Analisis Risiko Industri Nilam Menggunakan Metode Value At Risk (VAR) “Studi Kasus: Koperasi Industri Nilam Aceh, Kabupaten Aceh Jaya” - Richi Gunawan; Hasan Yudie Sastra; M. Dirhamsyah (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2023)
ABSTRACT Aceh Province is a province that has abundant natural resource potential, especially from the agricultural sector. One of them is patchouli which can be processed into goods of economic value, namely patchouli oil. Most of the people of Aceh work as farmers, especially in Aceh Jaya Regency. Currently, farmers in Aceh Jaya are intensively cultivating patchouli. However, so far the results of patchouli production and the patchouli refining process are still not optimal. The purpose of this study was to determine the impact of patchouli industry risk on the Aceh Patchouli Industry Cooperative (KINA) company in Aceh Jaya Regency. The method used in this study is value at risk (VAR) to analyze the impact of risk in order to reduce the company's potential losses. The results obtained in this study using the VAR method in the patchouli industry, among others, are nursery risk factors with a risk impact of Rp 1.335.650. Then found the impact of losses of Rp. 995.344 on disease and pest factors. Furthermore, it was found that the impact of the loss was Rp. 476.350 in the refining process. The biggest loss impact occurred in the nursery process of Rp. 1.335.650 and the smallest loss impact occurred in the refining process factor of Rp. 476.350.Keywords: Koperasi Industri Nilam Aceh, Value at Risk, Risk, Aceh Jaya Regency